2018
DOI: 10.2224/sbp.6619
|View full text |Cite
|
Sign up to set email alerts
|

How transformational leadership influences employee voice behavior: The roles of psychological capital and organizational identification

Abstract: We proposed a model with which we jointly tested psychological capital (PsyCap) as the key psychological mechanism through which transformational leadership (TL) affects employee voice behavior (VB), and examined the moderating effect of employees' organizational identification (OI) on the PsyCap–VB relationship. Data were collected from employees in companies located in southern China and a small group of Master of Business Administration students who were also in paid employment (N = 237). Results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 0 publications
3
28
1
5
Order By: Relevance
“…The dimensions of self-efficacy and toughness are significantly positively correlated with organizational performance ( p < 0.001), while the dimensions of optimism and hope are significantly positively correlated with organizational performance ( p < 0.05). This is consistent with the research results of Wang et al (2018) , suggesting that all dimensions of entrepreneur psychological capital can promote the improvement of enterprise performance, but the dimensions of self-efficacy and toughness have higher positive influence than the dimensions of hope and optimism. This may be because the dimension of optimism and hope is the self-confident expression of entrepreneurs themselves, which can promote entrepreneurs to carry out innovative activities but cannot guarantee the quality of activities ( Lucky, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…The dimensions of self-efficacy and toughness are significantly positively correlated with organizational performance ( p < 0.001), while the dimensions of optimism and hope are significantly positively correlated with organizational performance ( p < 0.05). This is consistent with the research results of Wang et al (2018) , suggesting that all dimensions of entrepreneur psychological capital can promote the improvement of enterprise performance, but the dimensions of self-efficacy and toughness have higher positive influence than the dimensions of hope and optimism. This may be because the dimension of optimism and hope is the self-confident expression of entrepreneurs themselves, which can promote entrepreneurs to carry out innovative activities but cannot guarantee the quality of activities ( Lucky, 2018 ).…”
Section: Discussionsupporting
confidence: 91%
“…The ultimate objective of highly identified employees is to do what is best for the organization and its stakeholders. The existing research also suggests that highly identified employees raise their voice for the betterment of the organization ( Qi and Ming-Xia, 2014 ; Wang et al, 2018 ). Identified individuals consider organizational harm as personal harm, and they are willing to deviate from rules to protect their organization ( Zuber, 2015 ).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…Second, Zare meta-analysis study discovered that previous researchers focused more on the big five personality factors which influence employee voice resulting on the gap in exploring other individual factors (Zare & Flinchbaugh, 2018). Third, literature reviews have explained that the antecedents and consequent of employee voice have not made personal resources influential enough to employee voice (Bottero, 2013;Morrison, 2011Morrison, , 2014Chamberlin, Newton & LePine, 2017;Wang & Zheng, 2018). In line with conservation resources (COR) are there any differences in terms of demographic diversity in employee voice?…”
Section: Introductionmentioning
confidence: 99%